Effect of glutamine, glutamic acid and nucleotides on the turnover of carbon (δ13C) in organs of weaned piglets - Amorim, Alessandro Borges; Berto, Dirlei Antonio [UNESP]; Saleh, Mayra Anton Dib [UNESP]; Telles, Filipe Garcia [UNESP]; Denadai, Juliana Célia [UNESP]; Sartori, Maria Márcia Pereira [UNESP]; Luiggi, Fabiana Golin [UNESP]; Santos, Luan Sousa [UNESP]; Ducatti, Carlos [UNESP] (Asian Australasian Association of Animal Production Societies, 2016)
Morphological and physiological alterations occur in the digestive system of weanling piglets, compromising the performance in subsequent phases. This experiment aimed at verifying the influence of glutamine, glutamate and nucleotides on the carbon turnover in the pancreas and liver of piglets weaned at 21 days of age. Four diets were evaluated: glutamine, glutamic acid or nucleotides-free diet (CD); containing 1% glutamine (GD); containing 1% glutamic acid (GAD) and containing 1% nucleotides (ND). One hundred and twenty-three piglets were utilized with three pigs slaughtered at day zero (weaning day) and three at each one of the experimental days (1, 2, 4, 5, 7, 9, 13, 20, 27, and 49 post-weaning), in order to collect organ samples, which were analyzed for the δ13C isotopic composition and compared by means of time. No differences were found (p>0.05) among treatments for the turnover of the 13C in the pancreas (T50% = 13.91, 14.37, 11.07, and 9.34 days; T95% = 46.22, 47.73, 36.79, and 31.04 days for CD, GD, GAD, and ND, respectively). In the liver, the ND presented accelerated values of carbon turnover (T50% = 7.36 and T95% = 24.47 days) in relation to the values obtained for the GD (T50% = 10.15 and T95% = 33.74 days). However, the values obtained for the CD (T50% = 9.12 and T95% = 30.31 days) and GAD (T50% = 7.83 and T95% = 26.03 days) had no differences (p>0.05) among other diets. The technique of 13C isotopic dilution demonstrated trophic action of nucleotides in the liver.
Keywords: Liver; Pancreas; Pigs; Stable isotopes